Performing on the Razor’s Edge: On the Aesthetics of the Theatre of Martin McDonagh - Müller, Péter P. (Hungarian Journal of English and American Studies, 2020)
Since the emergence of naturalism in the theatre in the last decades of the nineteenth century the reality of an action on the stage has been put into a new context. The previous tradition of performance characterized by artificial, schematic solutions in gestures and speaking was replaced by direct presentation. Performance pretended that real events were taking place in an artificial, stylized context; that is, within the framework of the theatre. The first part of the essay discusses the connection between theatre and violence, starting from a historical and philosophical context and arriving at an aesthetic perspective which regards violence as a challenge for the theatrical representation. The second part studies stage violence in the plays of Martin McDonagh with the primary example of The Lieutenant of Inishmore. The third part summarizes the Hungarian reception of The Lieutenant of Inishmore and compares two productions which handle the staging of natural and brutal scenes quite differently. As the whole play has a metatheatrical feature, confronting theatre with the general problem of theatrical representation, it is relevant to see how this challenge is handled by the productions reviewed. (PPM)